Lean Six Sigma y mejora de la productividad en el servicio de reparación de equipos de minería en una empresa metalmecánica - Ingar Medina, Christian Abdul (2023)
The article discusses a proposal to improve the productivity of a metalworking company by implementing Lean Six Sigma (LSS). The company aims to reduce defects in the repair of heavy machinery components for mining activities. The study describes the simulation process of the original data to propose a limit for the defect level, effectiveness, and efficiency goals to achieve better productivity levels. The DMAIC system stages were used to define the productivity problem in repairing category V components. The original data revealed a Cp of 0.91 and a Cpk of −0.64. The simulation utilized KANBAN and HEINJUNKA tools, resulting in a Cp of 1.09 and a Cpk of 0.95. The study concludes that the LSS methodology is feasible and beneficial for metalworking companies.